Differential Recovery Migration across the Rural–Urban Gradient: Minimal and Short‐Term Population Gains for Rural Disaster‐Affected Gulf Coast Counties. (13th October 2019) - Curtis, Katherine J.; DeWaard, Jack; Fussell, Elizabeth; Rosenfeld, Rachel A.
Abstract: Places affected or threatened by extreme environmental disturbances confront a number of significant issues, including whether their populations will stay the same or change through migration. Research on Hurricanes Katrina and Rita shows some displaced residents returned to their disaster‐affected communities once the built environment was restored, new migrants settled in affected places as part of the rebuilding effort, and the regional migration system grew more urbanized and spatially concentrated during post‐disaster years. Research also shows that not all disaster‐affected places recovered their populations. Our study examines whether differential recovery is systematically patterned along the rural–urban gradient. Using U.S. Census Bureau estimates and IRS county‐to‐county migration data, we investigate whether the 2005 hurricane season differentially exacerbated or altered previous migration trends across a rural–urban gradient that incorporates proximity to metropolitan areas and disaster‐related housing loss. We find a rural–urban differential in Gulf Coast recovery migration: The disaster boosted migration among non‐metropolitan counties, yet these increases were smaller and short‐lived compared to the patterns found for metropolitan counties, most especially high loss metropolitan counties. Our findings encourage theories of environmental migration to incorporate spatial differentiation and scenarios of environmental changes to account for differential impacts on settlement patterns across the rural–urban continuum.